Agricultural R&D in Sub-Saharan Africa: An era of stagnation - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2006)
Following two decades of increasing investments, growth in public agricultural research spending (adjusted for inflation) largely stagnated in Sub-Saharan Africa during the 1980s and 1990s, at an average rate of about 1 percent per year. This continentwide trend masks significant variation among countries. During 1991–2000, about half the countries in our 27-country sample experienced a contraction in total agricultural research and development (R&D) spending. Declines often occurred during periods of political unrest or following the completion of large donor-funded projects. The majority of African agricultural research is still conducted by the public sector. The declining growth in public agricultural R&D investments has not been justified by the growing needs of the agricultural sector, nor counteracted by growth in investments by alternative suppliers, such as the private sector or international research centers. In addition, with its current investment patterns, Africa will probably miss out on most of the biotechnology advances that are being made in other regions in the world. Institutional reforms may have improved efficiency in a number of countries, but without a corresponding increase in financial support, such gains will be insufficient to turn the trends around. The funding base for African R&D urgently needs to be restored, with increased commitments from both governments and donors. This should go hand-in-hand with the pursuit of innovative funding mechanisms.